Spectroscopic and microscopic characterization of atmospheric particulate matter. Issue 6 (2nd November 2017) - Ahmed, Manan; Guo, Xinxin; Zhao, Xing-Min
ABSTRACT: The aim of this study was to investigate the chemical properties of atmospheric particulate matter collected during post biomass burning events from November to December 2015. The types of particulate samples collected from the study area were total suspended particulates (TSP) and particulates less than 2.5 µm (PM2.5 ). Multiple methods were used for the qualitative and quantitative characterization. Fifteen major and minor trace metal analyses were performed using acid digestion followed by inductively coupled plasma mass spectrometry analysis. Infrared spectroscopy was used for the identification of functional groups of organic compounds present in the samples. In addition, field emission scanning electron microscopy–energy dispersive X-ray spectroscopy was used for morphological characterization and microanalysis of individual particles. The average measured concentration of trace metals in TSP and PM2.5 follows the order of Zn > Fe > Al > Cu > Pb > Mn > V > Cr > Ni > Sn > As > Hg > Cd > Ag > Co. Enrichment factor analysis showed strong anthropogenic contributions of Hg, Ag, Zn, Cd, Pb, As, Cu, and Sn in the samples. Field emission scanning electron microscopy–energy dispersive X-ray spectroscopy shows that three types of particles were present that originated from crustal and anthropogenic sources. Furthermore, the infrared measurements indicate that most compounds were organic acids and aromatic hydrocarbons.